2016
DOI: 10.1080/03634523.2016.1259485
|View full text |Cite
|
Sign up to set email alerts
|

Public speaking versus hybrid introductory communication courses: exploring four outcomes

Abstract: The purpose of this study was to compare student growth in public speaking and hybrid introductory communication skills courses on four outcomes: public speaking anxiety, selfperceived communication competence, intercultural effectiveness, and connected classroom climate. This study also sought to find out whether there were differences in the achievement of outcomes and growth in each outcome by sex and ethnicity. Data from 908 participants utilized a within-subjects and between-subjects repeat measures desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The alpha coefficients in this sample were 0.94 at both T1 and T2 and the 7‐week test–retest reliability coefficient was r s (197) = 0.65. A test–retest reliability coefficient of this magnitude was expected, given the changing nature of the construct (Broeckelman‐Post & Pyle, 2017).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The alpha coefficients in this sample were 0.94 at both T1 and T2 and the 7‐week test–retest reliability coefficient was r s (197) = 0.65. A test–retest reliability coefficient of this magnitude was expected, given the changing nature of the construct (Broeckelman‐Post & Pyle, 2017).…”
Section: Methodsmentioning
confidence: 91%
“…Participants completed an online baseline survey (Time 1 [T1]) half‐way through their Fall 2018 semester (Week 7) that included the CCCI (completed in reference to a single STEM course the participant was enrolled in) and measures of SCCT constructs, including academic self‐efficacy, STEM interest, major belonging, and university belonging. Because CCCI scores have been shown to increase over time (Broeckelman‐Post & Pyle, 2017), participants also completed the CCCI about their same course at Time 2 (T2) 7 weeks later (Week 14). Participants' grade for the course they completed the CCCI in reference to was obtained through University records at the end of the Fall 2018 semester (Time 3 [T3]).…”
Section: Methodsmentioning
confidence: 99%
“…This is likely due in part to the small sample size and low power; to be included in this analysis, students had to complete both the pre- and the post-course survey, so only 17 unsheltered and 27 sheltered students remained for this analysis, resulting in exceptionally low observed power. However, an examination of the means and profile plots suggests that pathways students in both classes might not be getting the same reduction in PSA as other students (e.g., Broeckelman-Post and Pyle, 2017; Hunter et al, 2014), which suggests a possible inequity that needs to be addressed. Moreover, while the difference was not enough to be significant, students enrolled in unsheltered sections had higher mean PSA scores across the semester, which suggests that they might be experiencing greater anxiety in the course, though we do not know whether this might be due to feeling a stronger need to assimilate into an unsheltered classroom environment, a perception of difference, greater efforts to be perceived as relatable, the extra burden of code switching (Ellwood, 2008), or other factors.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, CA and PSA also have a state component that is related to the situation or context in which a person is speaking; previous research has shown that factors such as audience size, whether the speech is being graded, audience response, and type of delivery can impact the level of CA or PSA (Bodie, 2010). Although state CA and PSA can never be completely mitigated since they are heavily influenced by an individual’s level of trait CA and PSA (Harris et al, 2006), there are several treatments that can successfully reduce PSA, including communication orientation modification (COM) therapy, cognitive modification, performance feedback, habituation, systematic desensitization, and getting skills training through taking a communication course (Bodie, 2010; Broeckelman-Post and Pyle, 2017; Finn et al, 2009; Hunter et al, 2014; McCroskey, 2009; Rubin et al, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Classes in which students perceive strong bonds with other course members are more connected than classes in which students are not as well bonded with their peers. While the CCCI is sometimes administered at a single time point, it has also been used in a pre–post format (Broeckelman‐Post & Pyle, 2017). The 18‐item CCCI scale has a single factor with evidence of validity and overall reliability of alpha = 0.94.…”
Section: Methodsmentioning
confidence: 99%